Crystallization kinetic of Er3+-doped BiO1.5-GeO2-BO1.5 glass-ceramic - Surapong Panyata (2018)
© 2018 In this work, glass-ceramics containing bismuth germanate doped with a rare-earth element of composition 58.4BiO1.5: 23.4GeO2: 18.2BO1.5: 0.15ErO1.5 was investigated for its kinetic parameters of transformations via available models. The activation energy for the crystallization (Ec) and the Avrami exponent (n) were determined under non-isothermal conditions using various models. X-ray diffraction (XRD) was used to obtain the phase formation. The morphologies of the obtained glass-ceramics were investigated by Scanning electron microscopy (SEM). It was found that the crystallization activation energy and Avrami exponent were dependent on the crystallization fraction (x). The calculated value of the Avrami exponent (n) by using Ozawa and Lu model indicated that the crystallization mechanism in this glass is between two and three-dimensional crystal growth. Doping of Er2O3 was found to improve modification of this Bi2GeO5 glass-ceramic embedded with a desired crystal dimension.